An Analysis of Implicit Meaning Found in Garfield Comic Strips (in May 2012 Edition) - Dwisnu, Erlian; Darma, Suci Dwina (International Journal of English and Applied Linguistics (IJEAL), 2023)
This research used descriptive method. It was used to get description about something by analyzing, interpreting, and concluding. In this case, the researcher described about implicit meaning found that exist in Garfield comic strips in May 2012 edition. In collecting the data, the researcher downloaded Garfield comic strip May 2012 Edition from official website of Garfield in http://www.Garfield.com. The results of this research showed that all of the comic strips contain implicit meaning. Furthermore based on the research question, the implicit meanings found in Garfield comic strips were divided into two types, they were particularized implicit and generalized implicit meaning, if we know the background knowledge of the Garfield we can use particularized implicit meaning, but if we didn’t knew we can use generalized implicit meaning. In this case, the comic strips were dominated by Particularized implicit meaning type. The total of Particularized implicit meaning were 19 comic strips, and the rests were 13 comic strips. The conclusion of this research is every edition of Garfield of comic strips has implicit meaning in every strip, so to know what the implicit meaning in every strip is we must know the background knowledge of Garfield. The researcher expects the result of this research will be useful for the english students who need the result of this research as references in learning pragmatics. The researcher also hopes that this research will inspire other researcher to analyze the implicit meaning in other comic’s strips.